Penggunaan Rebusan Daun Sirsak terhadap Penurunan Tekanan Darah Penderita Hipertensi - Juli Andri; Padila Padila; Ramadhan Trybahari Sugiharno; Kakalita Anjelina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to compare the use of soursop leaf decoction to reduce blood pressure in hypertension sufferers in the Work Area of the West Lingkar Health Center, Bengkulu City. This type of research is a quasi-experimental design with one group pre-test and post-test design. The results showed that the average systolic blood pressure before being given soursop leaf decoction was 146.67 mmHg to 140.13 mmHg, while the diastolic blood pressure was 85.07 to 80.93 mmHg. The statistical test results showed that the p-value of systolic blood pressure was 0.008 and diastolic blood pressure was 0.038. In conclusion, there was a decrease in systolic and diastolic blood pressure before and after the soursop leaf decoction intervention. Keywords: Hypertension, Soursop Leaf Decoction, Blood Pressure